Dynamic Innovation Capabilities and their Impact on Export Performance in Times of Economic Crisis - Ledesma-Chaves, Pablo; Arenas-Gaitán, Jorge (Review of Business Management, 2022)
Purpose– To determine the mediator role of innovative dynamic capabilities in performance in the internationalisation strategy of firms during periods of economic crisis. Theoretical framework– We base ourselves on the Theory of Dynamic Capabilities, as a response to the environment produced by an economic crisis. Two firm models are analysed in accordance with their internationalisation strategy: born-global and gradual internationalisation firms. Design/methodology/approach– We propose two hypotheses which are tested with a sample of 145 Spanish exporting firms. We use a structural equations model (SEM)- Partial Lead Squares (PLS) and PLS-MGA to compare the results among born-global and gradual internationalisation firms. Findings–Firstly, innovation capability is necessary for entering new markets to lead to improvements in the export performance. Secondly, there exist significant differences between born-global and gradual internationalisation firms. Research, Practical & Social implications– The analysis makes management contributions for the improvement in the use of skills and resources in firms in periods of profound variation of the environment, indicating for managers the importance of advancing in a process of creation and culture of dynamic capabilities. Originality/value– The study makes contributions regarding the role of innovative dynamic capability as an enhancer of international results in periods of economic crisis. It also contributes a novel form of capturing the dynamic character of the innovation capability. Keywords - Crisis, dynamic capabilities, born-global, exporting, innovation.